Threat of pain influences social context effects on verbal pain report and facial expression - Vlaeyen, Johan W.S.; Hanssen, Marjolein; Goubert, Liesbet; Vervoort, Tine; Peters, Madelon; van Breukelen, Gerard; Sullivan, Michael J.L.; Morley, Stephen (Behaviour research and therapy, 2009)
Current theoretical models of pain catastrophizing have diverging predictions regarding the role of social context and perceived threat on pain expression. The communal coping model of catastrophizing predicts that high pain catastrophizers display more pain expression in the presence of another, regardless of the threat value of the pain, while a cognitive appraisal model predicts high pain catastrophizers to express more pain when pain has increased threat value, regardless of social context. A 2 × 2 factorial design was used to test the validity of both predictions. Healthy participants with varying levels of pain catastrophizing were exposed to a cold pressor task, consisting of a 60 s immersion and 60 s recovery period. Interestingly, the immersion results revealed that beyond and independent from the effects of pain catastrophizing, the effect of threat on verbal pain report and facial expression was dependent on social context and vice versa. In a threatening context, perceived threat of pain mediated the inhibitory effect of social presence on pain expression, suggesting that the observer acted as a safety signal. In the recovery period, social presence enhanced facial expression, but only when no threat was induced. The results are discussed in terms of the dynamic interaction between social context and threat appraisals.